2022
DOI: 10.1007/s10584-021-03304-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective coastal adaptation needs accurate hazard assessment: a case study in Port Resolution, Tanna Island Vanuatu

Abstract: Developing countries face risks from coastal hazards that are being amplified by climate change. The selection of effective adaptation interventions to manage these risks requires a sufficiently accurate assessment of the coastal hazard at a given location. Yet challenges remain in terms of understanding local coastal risks given the coarseness of global wave models and the paucity of locally scaled data in most developing countries, including Small Island Developing States (SIDS) like Vanuatu. This paper aims… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Data limitations for the Pacific region also limit down-scaled assessments of climate risk. For instance, Faivre et al (2022) completed a hazard assessment in Port Resolution Bay, Vanuatu and found very limited data of sufficiently high resolution to model coastal processes effectively, leading to the risk of recommending maladapted approaches. In this example available wave data generated unrealistically high predictions of wave height within the bay, which if taken on face value would lead to a recommendation for extensive and expensive engineering adaptation for coastal protection despite these solutions being likely to fail to prevent ongoing cliff erosion, even under worst case scenarios associated with a Category 5 tropical cyclone.…”
Section: Ecosystems and Economiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data limitations for the Pacific region also limit down-scaled assessments of climate risk. For instance, Faivre et al (2022) completed a hazard assessment in Port Resolution Bay, Vanuatu and found very limited data of sufficiently high resolution to model coastal processes effectively, leading to the risk of recommending maladapted approaches. In this example available wave data generated unrealistically high predictions of wave height within the bay, which if taken on face value would lead to a recommendation for extensive and expensive engineering adaptation for coastal protection despite these solutions being likely to fail to prevent ongoing cliff erosion, even under worst case scenarios associated with a Category 5 tropical cyclone.…”
Section: Ecosystems and Economiesmentioning
confidence: 99%
“…In this example available wave data generated unrealistically high predictions of wave height within the bay, which if taken on face value would lead to a recommendation for extensive and expensive engineering adaptation for coastal protection despite these solutions being likely to fail to prevent ongoing cliff erosion, even under worst case scenarios associated with a Category 5 tropical cyclone. The most appropriate intervention identified by Faivre et al (2022) was revegetation of clifftops to reduce erosion, a solution that may be lower in immediate and ongoing costs and come with numerous additional ecological and social co-benefits.…”
Section: Ecosystems and Economiesmentioning
confidence: 99%